The cyclicality of government expenditure and wagner's law - case of Czech Republic, Slovakia, Hungary, Bulgaria and Romania - Szarowská, Irena (Univerzita Pardubice, 2012)
The importance of government expenditure management has increased during the last years. This paper provides empirical evidence on the cyclicality and the relationship between government expenditure and output in five European Union members in a period 1995–2009. We use Johansen cointegration test and the error correction model and analyze annual data on government expenditure in compliance with the COFOG international standard. The results confirm that the government expenditure functions are procyclical in most countries (91% cases in the sample). Output and government expenditure are cointegrated at least for four from ten expenditure functions in every country (four in the Czech Republic and Hungary, five in Bulgaria, seven in Slovakia and eight in Romania) and it implies a long-term relationship between government expenditure and output. Average value of long-run elasticity coefficients is 1.72 for all expenditure functions, 1.16 for total government expenditure. Conclusions about the short-run relationship between expenditure and output are not unambiguous due to a relatively low statistical significance. However, the coefficient values (average is 3.14) confirm the voracity hypothesis, as they suggest that in response to a given shock to real GDP, government expenditure will rise by even more in percentage points.
Keywords: government expenditure; cyclicality; voracity effect; long-run elasticity; short-run elasticity